Comparative Efficacy and Tolerability of Imiquimod 3.75% Cream vs 5-Fluorouracil 4% cream in the Treatment of Actinic Keratosis: A Split-Face Study - Cesare Ariasi; Carola Romanò; Cesare Tomasi; Gaetano Licata; Davide Geat; Piergiacomo Calzavara-Pinton; Mariachiara Arisi (Dermatology Practical & Conceptual)
Introduction: Actinic keratosis (AK) is a common precancerous skin lesion that arises on chronically UV-exposed skin and can progress to keratinocyte carcinoma. Objective: The aim of this study is to compare efficacy, safety, local skin reaction, time to wound closure, and patient preference of imiquimod (IMQ) 3.75% vs 5-fluorouracil (5-FU) 4% cream treatment for AKs. Methods: Two symmetrical contralateral areas of approximately 25 cm2 harboring a similar (≥5) number of AKs were selected and randomly assigned to IMQ 3.75% or 5- FU 4% cream treatment. The total number of AKs for each patient, was evaluated at baseline (T0) and 90 days after the end of treatments (T1). Local skin reaction (LSR) score was registered the day after the end of both treatments. Complete remission rate of lesions, cosmetic outcome, and patient preference of treatment were assessed after 90 days (T1). Results: The mean variation (ΔT0-T1) of AKs was not significantly different in patients treated with IMQ 3.75% and 5-FU 4% (p=0.35). The mean LSR was not significantly different for patients treated with IMQ 3.75% and 5-FU 4% (p=0.63). No difference in cosmetic outcome was observed in the 2 groups. Patient preference was equally distributed between the treatments. The mean time to wound closure after the end of the treatment was similar after IMQ 3.75% as compared to 5-FU 4% (p=0.83). Conclusions: This study reports a non-superiority of efficacy, tolerability, wound-healing time, and cosmetic outcome of topical IMQ 3.75% treatment compared to topical 5-FU 4% treatment in AK management.